2020
DOI: 10.1038/s12276-019-0359-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei-derived extracellular vesicles attenuate the intestinal inflammatory response by augmenting the endoplasmic reticulum stress pathway

Abstract: Lactobacillus paracasei is a major probiotic and is well known for its anti-inflammatory properties. Thus, we investigated the effects of L. paracasei-derived extracellular vesicles (LpEVs) on LPS-induced inflammation in HT29 human colorectal cancer cells and dextran sulfate sodium (DSS)-induced colitis in C57BL/6 mice. ER stress inhibitors (salubrinal or 4-PBA) or CHOP siRNA were utilized to investigate the relationship between LpEV-induced endoplasmic reticulum (ER) stress and the inhibitory effect of LpEVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 57 publications
(56 reference statements)
5
68
0
Order By: Relevance
“…IL-10 and TGF-β mainly mediate the negative regulation of inflammatory responses by suppressing the production of pro-inflammatory cytokines [ 55 , 56 ]. Similar suppression of pro-inflammatory cytokines and activation of anti-inflammatory cytokines induced by L. paracasei -derived EVs have also been observed with LPS-challenged human colon cancer cells [ 15 ]. Furthermore, several studies have demonstrated that probiotics-derived EVs controlled inflammatory responses by modulating the cytokine production in the host’s immune cells [ 31 , 42 ].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…IL-10 and TGF-β mainly mediate the negative regulation of inflammatory responses by suppressing the production of pro-inflammatory cytokines [ 55 , 56 ]. Similar suppression of pro-inflammatory cytokines and activation of anti-inflammatory cytokines induced by L. paracasei -derived EVs have also been observed with LPS-challenged human colon cancer cells [ 15 ]. Furthermore, several studies have demonstrated that probiotics-derived EVs controlled inflammatory responses by modulating the cytokine production in the host’s immune cells [ 31 , 42 ].…”
Section: Discussionsupporting
confidence: 60%
“…Only recently has it been increasingly interested in the mechanism of EVs secretion by which probiotics and commensal microbiota communicate with the host. Previous studies have revealed that EVs derived from several probiotics and commensal bacteria, such as Bacteroides fragilis [ 42 ], Akkermansia muciniphila [ 43 ], Escherichia coli Nissle 1917 [ 44 ], Bifidobacterium longum [ 45 ] and Lactobacillus paracasei [ 15 ], exerted similar effects as their parental bacteria. Consistent with these studies, we discovered that L. reuteri BBC3 could produce relatively high quantities of EVs, and treatment of broiler chicks with LrEVs reproduced the protective effects of L. reuteri BBC3 on LPS-induced lower performance and intestinal injury and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…these effects seem to be related to multiple mechanisms, such as the reduction of NO‐production and the amelioration of endoplasmic reticulum stress. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of Fusobacterium activates UPR and promotes inflammation in UC patients (72). Probiotic bacteria such as Lactobacillus paracasei ameliorated intestinal inflammation through ER stress-UPR pathway (73). On the contrary, Lactobacillus acidophilus mitigated intestinal inflammation by suppressing NF-kB and thereby inhibiting ER stress (74).…”
Section: Microbiota Er Stress and Inflammationmentioning
confidence: 99%